2016
DOI: 10.18632/oncotarget.9479
|View full text |Cite
|
Sign up to set email alerts
|

Moderate and strong static magnetic fields directly affect EGFR kinase domain orientation to inhibit cancer cell proliferation

Abstract: Static magnetic fields (SMFs) can affect cell proliferation in a cell-type and intensity-dependent way but the mechanism remains unclear. At the same time, although the diamagnetic anisotropy of proteins has been proposed decades ago, the behavior of isolated proteins in magnetic fields has not been directly observed. Here we show that SMFs can affect isolated proteins at the single molecular level in an intensity-dependent manner. We found that Epidermal Growth Factor Receptor (EGFR), a protein that is overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 49 publications
(46 reference statements)
2
41
1
Order By: Relevance
“…For 9 T SMF, which is relevant to the 9.4 T MRI at periclinal stage, the decreased cellular ATP levels should also cause some caution. On the other hand, this might be a potential way to inhibit cancer cell proliferation, which is consistent with our previous findings that 9 T SMF could inhibit some human cancer cell proliferation [Zhang et al, ]. However, our previous results also show that 1 T SMF could inhibit multiple cancer cell proliferation [Zhang et al, , , ], which apparently cannot be explained by the increased ATP levels induced by 1 T in this study.…”
Section: Discussionsupporting
confidence: 92%
“…For 9 T SMF, which is relevant to the 9.4 T MRI at periclinal stage, the decreased cellular ATP levels should also cause some caution. On the other hand, this might be a potential way to inhibit cancer cell proliferation, which is consistent with our previous findings that 9 T SMF could inhibit some human cancer cell proliferation [Zhang et al, ]. However, our previous results also show that 1 T SMF could inhibit multiple cancer cell proliferation [Zhang et al, , , ], which apparently cannot be explained by the increased ATP levels induced by 1 T in this study.…”
Section: Discussionsupporting
confidence: 92%
“…NIH-3T3 cells have been reported to be affected by 7-17 T SMFs [15] but CHO cells were shown to be irresponsive to SMFs ranging from moderate intensity SMFs to 13 T ultra-high SMFs in both ours and other people's studies [4, 7, 8]. Here we found that at high density, 1 T SMF reduced NIH-3T3 cell number but has minimal effects on CHO cells (Figure 4), which is consistent with previous reports.…”
Section: Resultsmentioning
confidence: 84%
“…We made a CHO cell line that stably overexpresses EGFR with a FLAG tag (CHO-EGFR cells) [4]. Here we examined them for their responses to 1 T SMF at different cell densities.…”
Section: Resultsmentioning
confidence: 99%
“…We found that 4 hr of exposure does not increase the non-lateral spindles (Figure 4B; Figure 4—source data 1) as 27 T SMF. We also tested 9 T SMF provided by a superconducting magnet (Zhang et al, 2016) and found that 4 hr of 9 T exposure does not increase the non-lateral spindles either (Figure 4C; Figure 4—source data 2). However, although exposure for a prolonged time of 3 days to 0.05 T or 1 T SMFs still had no effect (Figure 4D; Figure 4—source data 3), 9 T SMF treatment for 3 days could perturb spindle orientation (Figure 4E; Figure 4—source data 4).…”
Section: Resultsmentioning
confidence: 97%